PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA IV UNIT USAHA BALIMBINGAN - Ayu Suandani; Darwin Lie; Marisi Butarbutar; Nana Triapnita Nainggolan (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
The formulation of this research problem is how the influence of motivation and work environment on employee performance at PT Perkebunan Nusantara IV Balimbingan Business Unit. The research method used in this paper is literature research and field research. Its population is employees PT Perkebunan Nusantara IV Balimbingan Business Unit amounted to 59 people. Given the number of respondents less than 100 people to answer the quetionaiere that the author distributed and the availability of time of the author and for the accuracy of the results of research. The data used is data by qualitative and quantitative data, and data collection techniques by questionnaire, interview and documentation. Then the technique of data analysis using qualitative descriptive method and quantitative descriptive method. Result of analysis from linear regresi modestly that is Ŷ=8,697 + 0,809X1 + 0,6439X2 meaning there are positive influence between motivation and work environment on employee performance. The strength of relationship between the variables is very strength, that is r= 0,775. From coefficient determinasi can be explainable high low employee performance 60 %, and the rest 40 % explained by other factor not discussed in this study. From result of processing and calculation of questionnaires,the authors get the assumption that the motivation and work environment applied PT Perkebunan Nusantara IV Balimbingan Business Unit . This matter is proved by hypothesis test either simultaneously where result test the fhitung (42,034) > ttabel (3,16) and which significant 0,000 < alpha 0,05. Keywords: Motivation, Work Environment and Employee Performance